2018
DOI: 10.1007/s10886-018-0945-1
|View full text |Cite
|
Sign up to set email alerts
|

Acylated Quinic Acids Are the Main Salicortin Metabolites in the Lepidopteran Specialist Herbivore Cerura vinula

Abstract: Salicortin is a phenolic glucoside produced in Salicaceae as a chemical defense against herbivory. The specialist lepidopteran herbivorous larvae of Cerura vinula are able to overcome this defense. We examined the main frass constituents of C. vinula fed on Populus nigra leaves, and identified 11 quinic acid derivatives with benzoate and/or salicylate substitution. We asked whether the compounds are a result of salicortin breakdown and sought answers by carrying out feeding experiments with highly 13 C-enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
(52 reference statements)
2
23
0
Order By: Relevance
“…e UV spectrum of compounds 1-3 showed λ max at 327/307, 298 (shoulder), and 242 nm, which indicated that compounds 1-3 were hydroxycinnamic acid derivatives. [26,27], the position of caffeoyl substitution can be determined by the analysis of the chemical shift and coupling constants of the oxygenated methine protons of the quinic acid core, in which the H-5 signal showed a ddd type peak with coupling constants at 8.0-9.0 Hz, 8.0-9.0 Hz, and 3.0-5.0 Hz, while the H-3 signal had a small coupling constant and showed a brd or brs type peak. Compounds 4 and 5 were identified as chlorogenic acid (4) and 3-Ocaffeoylquinic acid (5).…”
Section: Procedures Of Constituent Identificationmentioning
confidence: 99%
“…e UV spectrum of compounds 1-3 showed λ max at 327/307, 298 (shoulder), and 242 nm, which indicated that compounds 1-3 were hydroxycinnamic acid derivatives. [26,27], the position of caffeoyl substitution can be determined by the analysis of the chemical shift and coupling constants of the oxygenated methine protons of the quinic acid core, in which the H-5 signal showed a ddd type peak with coupling constants at 8.0-9.0 Hz, 8.0-9.0 Hz, and 3.0-5.0 Hz, while the H-3 signal had a small coupling constant and showed a brd or brs type peak. Compounds 4 and 5 were identified as chlorogenic acid (4) and 3-Ocaffeoylquinic acid (5).…”
Section: Procedures Of Constituent Identificationmentioning
confidence: 99%
“…Hence, the apparent lack of CA defensive function is the integrated outcome of CA’s defensive and detoxification functions. Previously, the quinic acid moieties of CA were reported as conjugated to saligenin, a defensive phenolic glucoside in salicaceous plants, in the frass of another lepidopteran specialist herbivore ( 31 ), suggesting that several lepidopteran herbivores can use CA as a versatile detoxification agent. In short, the specialist herbivore M. sexta uses two distinct defensive compounds to detoxify each other.…”
Section: Resultsmentioning
confidence: 99%
“…Quinic acid was first discovered in the ethanol extract of RAS and the relative content reached 21.23%. Studies have shown that quinic acid has the effect of enhancing bile, reducing fat, detoxifying the liver, and preventing fatty liver [10,11]. In addition, after analyzing the volatile substances in the ethanol extract of RAL, it is found that effective biopharmaceuticals such as 2-myristynoyl pantetheine, benzoic acid, 4-hydroxy-3,5-dimethoxy-and 9, 12-octadecadienoic acid (z, z)-,what's more, there is also a substance phenol, 2, 2-methylenebis[6-(1, 1-dimethylethyl)]-4-methyl-that can be used as a phenolic antioxidant and an antioxidant in petroleum products, which is a good bioenergy substance.…”
Section: Volatile Compositional Diversity In Different Extracts From Ral and Rasmentioning
confidence: 99%